AN ANALYSIS OF USING ONLINE CONFERENCE TOOS IN ELT DURING THE PANDEMIC COVID19 AT UNIVERSITAS MUHAMMADIYAH MAKASSAR - Syam, St. Syahruni; Ul Haq, Muhammad Zia; Sangkala, Ismail (FKIP Unismuh Makassar, 2023)
This study used the Post Study System Usability Questionnaire (PSSUQ) method to assess and find out perceptions based on their experiences in using online conferencing tools, especially ELT during the covid19 pandemic at Universitas Muhammadiyah Makassar. The participants in this study were students of English education at the Universitas Muhammadiyah Makassar, students of the English education department. Purposive sampling is used by the current researcher. Research activities will be carried out through the stages of evaluating which classes in 2019 are very intense using Zoom as an ELT learning media, then distributing questionnaires to students as respondents, and finally analyzing the scores obtained and drawing conclusions regarding the use of Zoom as an ELT learning media at Universitas Muhammadiyah Makassar during the covid19 pandemic. The Post Study System Usability Questionnaire (PSSUQ) method is used to assess a system or find out the extent of user experience in order to get an overall impression of the experience of users or end users of a system. The rule in the PSSUQ score is that the lower the score obtained from the results of the questionnaire, the better the system will be.